Pengaruh Kepribadian Right Wing Auhtoritarian Personality, Religious Orientation Dan Identitas Sosial Terhadap Prasangka Agama Pada Mahasiswa - Hilman Fauzi; Ima Sri Rahmani (Fakultas Psikologi UIN Syarif Hidayatullah Jakarta, 2017)
The aim of this study is to explore the influence of right wing authoritarian, religious orientation and social identity against religious prejudice on students. By using accidental sampling, 200 participantstook part in this research. Some factors are examine in this research, right wing auhtoritarianpersonality, religious orientation, and social identity. The instrument that are used in this research isPrejudice Scale, Religious Orientation Scale (ROS), and Social Identity Scale. Confirmatory factoranalysis (CFA) is used to examine the validity of the scale. Multiple regression analysis is used fordata analysis. The result showed that there is significant effect of right wing authoritarianpersonality, religious orientation, and social identity toward religious prejudice among student asmany 17.5%. The result from minor hypotheses test showed that there are three variables that aresignificantly affect religious prejudice, they are submission, extrinsic and sense of belonging. Overall,it can be concluded that right wing authoritarian personality, religious orientation, and socialidentity significantly affect religious prejudice. Future research is suggested to explore other variablesthat might affect religious prejudice. DOI: 10.15408/tazkiya.v22i1.8158